KEBERADAAN ARTEFAK GERABAH DI DESA MELIKAN - Novita Wahyuningsih (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article is the result of the analysis from a study about earthenware jugs in the village of Melikan. The method used forthis research is a qualitative research method. This qualitative research method is descriptive in nature since it describes andexplains a particular phenomenon. The location of the research is the village of Melikan in the Wedi district of Klaten. Theapproach used is that of hermeneutic interpretation. The problems addressed in the research are: 1) What are the origins of theearthenware jug? 2) What are the developments and forms of earthenware jugs in Indonesia? and 3) How do earthenwarejugs continue to exist in the village of Melikan? The aim of this research is to discover the origin of the earthenware jug, itsdevelopments and forms in Indonesia, and its existence in the village of Melikan. The benefits of the research are that it willprovide new information and make a contribution to literature on the subject of earthenware jugs, and it is hoped that it willcomplement other existing studies. The results of this research show that the earthenware jug as a container for drinking waterhas its origins in the kundika from India; there are two kinds of development of the earthenware jug in Indonesia, namelytraditional earthenware jugs and new earthenware jugs; the existence of the earthenware jug in the village of Melikan isstill evident to this day, with a number of new types, shapes, functions, uses, and also new developments in the materials used,the manufacturing technology, and marketing process. To date there are 30 different types of earthenware jug in the villageof Melikan.Keywords: jug, earthenware, Melikan village.